Copy number variants in fetuses with isolated and non-isolated increased nuchal translucency detected by chromosomal microarray analysis - Huang, Shuxian; Wu, Heming; She, Lingna; Liu, Lina (Frontiers in Genetics, 2025)
ObjectiveThe purpose of this study was to explore the detection rate of chromosomal copy number variants (CNVs) in fetuses with isolated and non-isolated increased nuchal translucency (NT) by chromosomal microarray analysis (CMA).MethodsA retrospective study was conducted on 211 fetuses with increased NT diagnosed prenatally at Meizhou People’s Hospital from November 2022 to June 2025. Interventional prenatal CMA testing was conducted on these fetuses. The detection rates of chromosomal abnormalities in fetuses with isolated and non-isolated increased NT, and fetuses with different NT thicknesses (2.5-3.4, 3.5-4.4, and ≥4.5 mm) were analyzed.ResultsAmong the fetuses, hromosomal aneuploidy, pathogenic or likely pathogenic (P/LP) CNVs, and variants of uncertain significance (VOUS) were detected in 23, 14, and 26 fetuses respectively, with a total detection rate of 29.9%. A total of 151 fetuses (71.6%) had increased NT, and 60 fetuses (28.4%) had non-isolated increased NT. There was a statistically significant difference in the detection rate of chromosomal abnormalities between the two groups (23.2% vs. 46.7%, χ2=11.311, p=0.001). In fetuses with isolated increased NT, with the increase of NT thickening, the rate of chromosomal aneuploidy shows an increasing trend. And there was statistically significant difference in detection rate of chromosomal aneuploidy in fetuses with different NT thicknesses (p=0.045).ConclusionsA notable difference existed in the detection rate of chromosomal abnormalities between fetuses with isolated and non-isolated increased NT. For those with isolated increased NT, chromosomal aneuploidy rates tended to rise with increasing NT thickness, while this trend was not observed for P/LP CNVs.